The effects of the electromagnetic fields on reproduction in rats - Aydin, Muhterem; Apaydin, Mukremin; Yuksel, Murat; Aydin, Mustafa (Indian Veterinary Journal, 2008)
In recent years, many studies were carried out on the possible effects of electromagnetic fields on human health. Several of these studies focused on electromagnetic fields from high voltage power lines in close proximation to people's residences (Henshaw, 2002; Robert, 1999). Controversy exists among researchers about the effects of electromagnetic fields in varying durations on various periods of gestation display some differences on implantation levels, litter survival rate, average number of litters and hormone levels etc. in rats (Dupont, 2005; Zusman et al., 1990; Huuskonen et al., 200/1; Rodriguez et al., 2003; Ryan et al., 1996). This study aims to examine the effects of exposure to electrical and electromagnetical fields (originating from 170 kV high-frequency power lines) on reproduction in rats.
Keywords: Frequency Magnetic-Fields; 60 Hz; Exposure; Cycle